Identifying the Interdependence Between Us Monetary Policy and the Stock Market - Hilde C. Bjørnland; Kai Leitemo (Norges Bank, 2008)
We estimate the interdependence between US monetary policy and the S&P 500 using structural VAR methodology. A solution is proposed to the simultaneity problem of identifying monetary and stock price shocks by using a combination of short-run and long-run restrictions that maintains the qualitative properties of a monetary policy shock found in the established literature (Christiano et al., 1999). We find great interdependence between interest rate setting and real stock prices. Real stock prices immediately fall by 7-9 percent due to a monetary policy shock that raises the federal funds rate by 100 basis points. A stock price shock increasing real stock prices by one percent leads to an increase in the interest rate of close to 4 basis points.
hdl:11250/2497782
Keywords: E61; E52; E43; 330; VAR; monetary policy; asset prices; identification